Gastric jejunum intussusception and other high post-gastrectomy Reichel Polya precolic occlusions: our experience - Pataro, Arnaldo H; Pataro, Raúl E (Cirugía del Uruguay, 1973)
Gastrectomies performed totalled i350 cases; there were 6 cases of high jejunal postoperatory occlusions and only one patient died ( death rate: 16 % ) . Occlusions were due to adhesions and kinks of the efferent loop in 4 cases and of the afferent loop in another. The sixth case was caused by retrograde invagination of efferent- tip through jejuno-jejunal anastomosis in the lower part at 'the foot of gastrectomy.